Corporatizing security through champions, condos and credentials - Lippert, Randy (The Australian and New Zealand journal of criminology, 2019)
This paper argues that corporatization of security is distinct from related phenomena including commodification, privatization, and marketization. Corporatization refers to the spread of the corporate form and therefore to organization and governance, not ownership, and as corporatization expands in the security domain it raises troubling issues due to its secretive and undemocratic features. Corporatization’s conceptual purchase and these issues are shown through exploration of emergent security arrangements in three under-researched, disparate realms with growing global presence: public police sponsorship, private residential urban security, and public corporate security. These revealing realms of security corporatization are established and enhanced by specific techniques and organizational forms, including champions, condominiums, and credentials, respectively. The paper concludes with discussion of implications of corporatization of security for scholarly methods of inquiry and critique as well as for increasing accountability.